Utilization water hyacinth to reduce biological oxygen demand (BOD), chemical oxygen demand (COD), pH, odor and color of tofu liquid waste - Mangoloi Sinurat; Rosmayani Hasibuan; Nelma Hasibuan (Pascasarjana Universitas Negeri Medan, 2017)
There are a lot of tofu industries in Indonesia from small to large industries. The industrial activity produces waste. The content of organic substance in the liquid waste potentially pollute the environment, so waste treatment is needed before discharge into the environment. This study aims to determine the ability of water hyacinth to reduce the content of BOD, COD, odor, color and increasing pH of the tofu that produce in these factory. This research was conducted at the tofu’s factory Medan Ayahanda street and water hyacinth are taken around the river Deli Medan Maimon. BTKL (Balai Teknik Kesehatan Lingkungan) and Analis Department Health Polytecnic Medan are where analysis is done from January to August 2017. The method used to measure its value is BOD with DO Meter, COD with open Reflow method using COD Reactor tool, pH with pH meter, odor and color in a physical way. Based on the research results, water hyacinth proved effective can be used to reduce BOD and COD levels color, odor and raise pH on tofu liquid waste twith the same number of samples. Growing number of water hyacinth in the tofu liquid waste, it will be more effective to lower levels of BOD, COD , smell, color and raising pH.Key words: waste water tofu, water hyacinth, absorption